Revisitar Vieira no séc. XXI - O Poder da Palavra - Escritas, Artes e Ensino de Vieira vol. II - José Eduardo Franco (Outros Títulos, 2020)
"Revisiting Vieira in the 21st Century is a unique and necessary work, consisting of a fundamental set of reflections around ten nuclei, which allow us to visit the master in order to know him better in the light of modern times. And so we find, at each step, the demonstration of the geniality of the speaker and of the man of culture, as well as a constant appeal, which current events cannot forget, regarding the consecration of human dignity. The ten nuclei have a strong analytical and pedagogical sense, allowing us to know and understand a unique source in Portuguese culture: biography, historiography and reception - to integrate ourselves in the life path of the genial author; epistolography and interlocutors - to understand the importance of his intervention; theology and spirituality - to understand the fundamentals of what he tells us; visions of the future: prophetic work - to consider his capacity for anticipation; politics and society - to understand the importance of political commitment, in a time full of uncertainties and threats; sacred oratory and rhetoric: arts, uses and senses - to take care of the creation workshop of the unique artist; literature and art - to continue to scrutinize the enchanting capacity of the craftsman; polemic writings and the vision of the other - to deal with the courage and determination of the intellectual; science and nature - to realize the genuine attraction that he had for knowledge; and pedagogy and didactics - to put ourselves in the position of those who wish to learn the most from Vieira's lesson. "